Decoding Fan and Societal Sentiment: ABSA of The Saudi Pro League’s Recent Evolution - Alraimi, Dheya Ali Qasem; Paputungan, Irving Vitra (Department of Informatics Universitas Islam Indonesia, 2025)
The Saudi Professional League (SPL) has attained global recognition through its recruitment of high-profile international players, yet this rise has intensified public scrutiny regarding incidents involving these athletes, such as Controversies surrounding sportsmanship, provocative celebrations, verbal altercations with spectators. This study analyzes (4,884) Arabic-language posts from (2021 to 2024), employing Aspect-Based Sentiment Analysis (ABSA) and the fine-tuned MARBERT model. The findings reveal a dominant negative sentiment (71.9%) across the dataset, with 'Player-Conduct' and 'Disciplinary-Action' emerging as the most frequently discussed aspects. Co-occurrence and correlation analyses indicate that negative sentiment is closely tied to perceptions of inadequate governance and cultural misalignment within the SPL, further intensifying public dissatisfaction. This research underscores the duality of high-profile players as drivers of global visibility and sources of domestic tension, particularly within culturally sensitive contexts. By addressing these challenges, the SPL can mitigate reputational risks while harmonizing its international ambitions with domestic expectations. This study advances Arabic Aspect-based sentiment analysis in the sports domain and provides actionable insights to enhance ethical governance, align with cultural sensitivities, and strengthen stakeholder engagement, thereby supporting the SPL’s long-term credibility and growth.